Taxonomic Review of the Genus Didymocorypha Wood-Mason, 1877 (Mantodea: Eremiaphilidae) with description of a new species from India - Kamila, A. P.; Sureshan, P. M. (Zootaxa, 2024)
The genus Didymocorypha Wood-Mason, 1877 (Mantodea: Eremiaphilidae: Iridinae), distributed in the Oriental Region, is revised with data on morphology, ecology, distribution and life history. A new species, D. wayanadensis sp. nov., is described from three specimens from India. This new species is the first record of Didymocorypha from Kerala and Punjab states, India. A key to the world species of Didymocorypha is included.